Development Of A Polylactic Acid (PLA) Film With A Cinnamaldehyde Beta Cyclodextrin Complex For Packaged Cape Gooseberry (Physalis peruviana L.) (@limentech, Ciencia y Tecnología Alimentaria, 2024)
The cape gooseberry is a climacteric fruit harvested in Colombia, one of the leading exporters in the world. The conditions of temperature and relative moisture during storage decrease the titratable acidity and pH of the fruit, generating changes associated with fruit maturation that contribute to the fungal proliferation of the disease Botrytis cinerea. Conventional polymer-based packaging is used to commercialize and protect fresh cape gooseberries from mechanical damage. However, they create a suitable atmosphere for the propagation of fungi. In this paper, an active polymeric film with antimicrobial compounds and the capacity to inhibit the growth of Botrytis cinerea was developed. For the encapsulation technique, three ratios of the inclusion complex and polysorbate 80 were tested to obtain the PLA film. In both cases, the best ratio was determined to be 50:50, achieving an encapsulation efficiency of 71.41%. To evaluate the concentration of cinnamaldehyde inside the packaging, fresh fruits were placed in a rigid-base container with a flexible film on top alongside the polymeric films. The test was conducted at room temperature for three weeks. It was confirmed that the polymeric film provided a controlled release of the active compound, which resulted in a delay in the appearance of the fungus.
Keywords: antifungal; casting; encapsulation; postharvest